Study on organic matter depletion in argillaceous limestone of Leikoupo Formation of the Middle Triassic in the central Sichuan Basin: decoupling of organic matter development and preservation conditions under the background of saltwater algae control - Huang, Yuhan; Wei, Yan; Wen, Huaguo; Huo, Fei; Wu, Xueyan; Guo, Ruiyu; Liao, Yuntao; Ruan, Yunbo; Jiang, Huachuan (Frontiers in Earth Science, 2025)
The Anisian period of the Middle Triassic was a recovery period after the end Permian mass extinction. During this period, a set of organic rich limestone and shale were deposited in the Gypsum lagoon of the Leikoupo Formation in the Sichuan Basin, gradually evolving into a self-generated and self-stored reservoir. This oil and gas reservoir in the 2nd submember of 3rd member of the Middle Triassic Leikoupo Formation (T2l32) was excavated by the CT1 well in the central Sichuan region during recent explorations. However, the previously drilled limestone in Leikoupo Formation in the adjacent PY area has low organic matter abundance and not been able to form a reservoir, and this phenomenon has not been explained yet. To clarify the mechanism of organic matter enrichment in high salinity environments of T2l32 in the PY area, conducting comprehensive analysis using organic and inorganic geochemical techniques. The argillaceous limestone of T2l32 in the PY area is mainly deposited on the edge of the gypsum-limy lagoon, with low TOC values ranging from 0.11% to 0.34% and the kerogen of type I-II1. The RO value ranges from 1.16 to 1.36, with an average of 1.24, indicating that the source rock has reached a high maturity stage. Based on the combination of biomarker compounds and elemental geochemical techniques, it has been found that organic matter mainly comes from planktonic organisms in reducing seawater, accompanied by a small amount of terrestrial organic matter, and the selective enrichment of algae to the environment is also an important factor contributing to differences in organic matter enrichment in local areas. Furthermore, it can be recognized that the low organic matter abundance in argillaceous limestone in the PY area is controlled by multiple factors. Firstly, dry climate is not conducive to organic matter enrichment. Secondly, the mismatch between productivity conditions and organic matter preservation conditions results in insufficient original organic matter abundance. The decoupling of organic matter development and preservation conditions is the main cause of organic matter depletion in the research subjects. Research on the trend of marine producers towards favorable environments during this period can provide a case study for the enrichment of organic matter in high salinity environments.